2021
DOI: 10.1177/03635465211006480
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors in Concussion Events: A 5-Season Study in the French Top 14 Rugby Union Championship

Abstract: Background: Concussions are a source of major concern in rugby, and a limited number of studies have attempted to identify risk factors for these injuries. Purpose: To investigate the incidence of match concussion and associated risk factors, including individual workload, anthropometric variables, playing position, and season phase, in elite rugby union players. Study Design: Case-control study; Level of evidence 3. Methods: All concussions and explanatory variables were collected for every match over 5 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…The incidence rate of concussion was greater in Elite players than U18 or U22 players, which was consistent with the findings in other studies [ 7 9 , 21 ]. It is likely due to the greater momentum gained by heavier, taller players with high speed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The incidence rate of concussion was greater in Elite players than U18 or U22 players, which was consistent with the findings in other studies [ 7 9 , 21 ]. It is likely due to the greater momentum gained by heavier, taller players with high speed.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies reported that a tackle event is the most common cause of concussion, and 70% of tackle-related concussions occur in the tacklers [ 1 , 4 , 5 ]. Detailed analysis of tackles using video footage has become a standard method for investigating the cause of the injuries [ 4 9 ], and analyzing the body position and height of the tackle may be of value for reducing tackle-related concussion [ 1 , 4 , 5 , 10 17 ].…”
Section: Introductionmentioning
confidence: 99%